Economic Impact of Heavy Metals Accumulation in Aquacultured Tilapia Fish in Egypt (International Journal of Scientific Research and Management (IJSRM), 2024)
Fish can accumulate heavy metals in their bodies from water through direct consumption or absorption through the gills, skin, and digestive system. Consequently, these metals can be transferred to humans through the consumption of contaminated fish, which may pose serious health risks. Therefore, human consumption of fish contaminated with toxic metals can cause various diseases such as liver cirrhosis and kidney failure. The study aimed to measure the potential health risks of exposure to heavy metals that exceeded the maximum limits, identify the most accumulated heavy metals in farmed fish, and assess the economic impact of the accumulation of some heavy metal elements in farmed fish in Kafr El-Sheikh and Fayoum governorates. This was done by collecting samples from several fish farms. One of the key findings of the study was the presence of multiple heavy metal elements, with arsenic and magnesium being prominent in the samples from both governorates, exceeding permissible limits in Kafr El-Sheikh. It was found that the non-compliant production in Kafr El-Sheikh averaged around 416,000 tons, valued at approximately 10 million EGP, indicating inefficient utilization of this production. In Fayoum, the non-compliant production for export specifications averaged around 14,000 tons, valued at approximately 348,000 EGP, also highlighting inefficient utilization of this production.